CYBERBULLYNG DI ERA DIGITAL: DAMPAK, PENYEBAB DAN UPAYA PENANGGULANGAN - Nadra Zelina Putri; Zubaidah Lubis; Syakila Mawaddah Caniago; Lola Musfira; Adzkia Al Adha Nihayatun Nufus; Ria Wahyuni Malik; Kartika Sari Devi; Lisa Septia Dewi Br.Ginting (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Along with the development of internet technology and social media, it has an effect on the acceleration of the process of disseminating information. The rapid development of information technology can have a negative impact if not utilized properly. Currently, cases of cyberbullying are increasing and often occur through social media. One of the factors that can cause cyberbullying is from online activities, especially those carried out by children, either uploading content or commenting on content that is uploaded reactively. As a result, these cyberbullying incidents are increasingly widespread and have a serious impact on the emotional and mental well-being of adolescents. The purpose of this paper is to determine the causes of the rise of cyberbullying in the digital era among adolescents. The method used is a literature review by collecting and taking the essence of previous research and analyzing several sources that are relevant to the research topic. The results of the study show that cyberbullying has a significant psychological impact, such as mental stress to suicide. Therefore, the involvement of the government, society, and family is needed to create a safer and more responsible digital space